COVID-19 Traumatic Disaster Appraisal and Stress Symptoms Among Health Care Workers: Insights From the Yale Stress Self-assessment. Issue 11 (16th November 2022) - Olson, Kristine D.; Fogelman, Nia; Maturo, Laura; Alvarado, Javier; Ball, Samuel; Forray, Ariadna; Hu, Mary; Ivy, Michael; Kapo, Jennifer; Krystal, John; Mayes, Linda; Rohrbaugh, Robert; et al.
Abstract : The COVID-19 pandemic was an occupational hazard for healthcare workers. Stress symptoms in 8299 healthcare workers suggests potential adverse effects on quality of care, professionalism, retention, acute and chronic mental health conditions. Some healthcare workers experienced the pandemic as a traumatic event. Through machine learning, risk factors predicted escalating stress. Abstract : Objective: To determine to what extent did health care workers experience the pandemic as a severe stress event. Methods: This cross-sectional evaluation of 8299 health care workers, representing a 22% response rate, utilized machine learning to predict high levels of escalating stress based on demographics and known predictors for adverse psychological outcomes after trauma. Results: A third of health care workers experienced the pandemic as a potentially traumatic stress event; a greater proportion of health care workers experienced high levels of escalating stress. Predictive factors included sense of control, ability to manage work-life demands, guilt or shame, age, and level of education. Gender was no longer predictive after controlling for other factors. Escalating stress was especially high among nonclinical academics and clinical private practitioners. Conclusion: Findings suggest adverse effects on total worker health, care quality, professionalism, retention, and acute and chronic mental health.